How Important was Labor Reallocation for China's Growth? A Skeptical Assessment. (21st June 2017) - Ye, Longfeng; Robertson, Peter E.
Abstract: Numerous studies report the growth effects from labor reallocation in China to be in the order of 1–2 percentage points per year, which would appear to be a significant fraction of China's per capita income growth. We show that the total factor productivity gains are an order of magnitude smaller, at only 0.25 percentage points per year. There are two reasons for this difference. First, the majority of studies have used a decomposition method that effectively assumes linear production functions. This results in values that are much larger than the more appropriate Denison–Kuznets method. Second, we also allow for sectoral differences in human capital. We conclude that the gains from labor reallocation may have been a far less important source of China's growth than is conventionally thought.